Automated Women Distress Detection and Indicating System - Muneeswari, G; Banupriya, R; Meena, V; R. Vaishtnave, K (International Journal of Engineering and Technology, 2018)
As in modern world with increasing harassments towards younger women, there is a requirement for an automatic smart system to get rid of the dangerous situation. There are lot of crimes against women cases closed due to non-availability of evidences or the perpetrator escapes from crime. In order to avoid and prevent such pathetic situations, a new idea is proposed in this paper. In this proposed system along with the alert and panic information, victims can also initiate a voice call. We propose a system that could be easily started by the action of human. On initiation, voice call alert and a distress message with a longitude and latitude location will be sent to the pre-stored cell number and also updated on the server. The person is tracked along with which we implement sudden shocking mechanism to protect against any possible harassment.